Para além da ilusão: os limites da critica freudiana à religião - Claudia Maria Silva Moreira (2009)
Taking into acco that religion would lose its power and importance in the future, two questions have arisen: 1) Why hasnt the Freudian prediction been confirmed so far? 2) Would there be any aspects not contemplated in Freud`s critical analysis towards religion? The perception of the irreducible character of illusion led us to the conclusion that there could be other elements, besides imaginary aspects, in the religious adherence. According to Freuds elaborations, the psychological origin of the religious necessity lies in childhood helplessness. The analysis of childhood helplessness revealed that a part of this experience related to the satisfaction experience was not integrated by Freud in his critical analysis of the religious fact. The considerations in Moses and Monotheism (1939) confirm that the element neglected by Freud in his study of the religion is related to das Ding. This element could be the explanation for the power of religion beyond illusion